So from the text I'm reading:

If failure occurs in (k-1,k], with payment at time k, then K_{x}= k-1.

Random Variable Z_{X}=V^{Kx+1}, for K_{x}= 0, 1, 2,...

Expected value of random variable Z_{x}

A_{x}= E[Z_{X}] = \sum\limits_{k=1}^infinite v^{k}Pr(K_{x}= k-1)= \sum\limits_{k=0}^infinite v^{k+1}Pr(K_{x}= k)

I mainly need help understanding the last part for the A_{x }and how the two summation are the same. From my understanding, I think they're equal because the right side equation although k = 0, we are adding another v in to the equation.